Comparative Analysis of the Effectiveness of Wayside and Onboard Systems for Condition Monitoring and Fault Detection - NAFIZ IDLAN SALMAN; Musli Nizam Yahya; Norazman Abu Hassan (Progress in Engineering Application and Technology, 2025)
This paper offers a study that compares onboard condition monitoring systems and wayside condition monitoring systems in railways by assessing three factors: real-time monitoring, fault detection capabilities, and cost-effectiveness. Through the use of a qualitative thematic analysis of 52 academic excerpts, the study organises data based on the type of monitoring system and the performance trait within each type. The findings show that onboard systems outperform wayside systems with respect to real-time diagnostics and fault detection capabilities, particularly relevant to critical safety and reliability components (e.g., bearings and wheelsets). Wayside systems have the goal of being a more cost-effective way of fleet-wide monitoring using fixed location infrastructure and the onboard component of multiple trains at once, without the need to install anything on the train. The specific cost assessment highlighted that onboard systems, although highly capable, were three times more expensive over a six-year lifespan. This study has identified that both type of systems have their own strengths and weaknesses when compared to each other, so a hybrid approach may be the most useful in creating reliability, efficiency, and sustainability in railway condition monitoring.